Road traffic accidents: a lifetime financial blow the victim cripples under - Verma, Preeti; Gupta, S C; Misra, Sunil Kumar; Agrawal, Renu; Agrawal, Vishal; Singh, Gagan (Indian Journal of Community Health, 2015)
Introduction: WHO states that the proportion of deaths and casualty registrations of RTA cases represents only the tip of the iceberg. A similar tip of the iceberg phenomenon exists between the visible expenses incurred due to the accidents and the much larger invisible losses are there that imperceptibly disable the family budget. Objective: (1) To estimate the total expenditure on treatment of RTA cases and its proportion to their monthly family income on treatment.(2) To estimate the loss of wages of RTA cases and project the other losses.(3) To enquire reimbursement of losses of RTA cases. Materials and methods: A hospital based cross sectional study, conducted at ED and Hospital of S.N. Medical College, Agra. Data were collected by using semi structured questionnaire from RTA cases or their attendants. Results: Out of 425 admitted RTA cases, 318 (74.8%) had spent Rs > 5,000 on the treatment and 304(71.5%) had lost their wages Rs >1, 000. 73.2% had incurred hospital expenses from 1to10 times or even more of their monthly family income. About 1/4th cases recovered completely and 64.01% recovered with temporary physical deficit. 3.5% had health insurance. 75.8% cases had remained hospitalized for more than1 week or up to a month duration and a strong positive correlation (r = 0.83) was found between the length of stay in the hospital and the amount spent on the treatment. Conclusion: The financial assault suffered by the road traffic accident cases and their families even if they are treated in Government Hospital are so huge that cannot be ignored.